Sports traditions in ancient civilizations: a comparative analysis from Mesopotamia to pre-Islamic Arabia - Mohammed Insaf, Mohammed Ghous; Shehu, Fatmir (Sultan Abdul Halim Mu’adzam Shah International Islamic University (UniSHAMS) Sdn. Bhd., 2024)
Sports reflect the values and practices of civilisations, offering insights into diverse cultural, religious, and social dynamics. This article investigates the significance and evolution of sports within ancient civilisations, focusing on the Mesopotamian, Sumerian, Egyptian, Indian, Chinese, Greek, Roman, Southeast Asian, and pre-Islamic Arabian cultures. The study examines how these societies shaped and shaped sports, highlighting their roles in fostering physical fitness, enhancing strategic thinking, promoting community cohesion, and strengthening cultural identity. Employing a contextual analysis methodology, it draws on secondary sources, including journal articles, books, and reputable web resources, to explore these themes. Through comparative analysis, the findings reveal both commonalities in sports' societal functions and unique characteristics rooted in each civilisation's distinct worldview, thereby providing a comprehensive understanding of sports as a cultural phenomenon across ancient societies.